Equity valuation: CTT – Correios de Portugal, S.A. - Carvalho, Rodrigo Loureiro Henriques Gonçalves de (2016)
Agents of postal sector are facing significant challenges due to technological impact and recent liberalization of markets across the globe, leading to redefinition of most companies’ strategies. The purpose of this project is to provide an equity valuation on largest player of the postal sector: CTT – Correios de Portugal, S.A. This is a particularly interesting asset to study, as it underwent a privatization process which was highly debated, dividing opinions amongst its stakeholders. We deliver a detailed insight on postal sector and CTT Group and ground our valuation on an extensive literature review. Through the application of the discounted cash flow methodology, we have estimated an equity value, as at 31st December 2014, of €1.4b, corresponding to target price per share of €9.57.